2007
DOI: 10.1016/j.foodchem.2007.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Hazel (Corylus avellana L.) leaves as source of antimicrobial and antioxidative compounds

Abstract: Aqueous extracts of leaves of different hazel (Corylus avellana L.) cultivars (Cv. M. Bollwiller, Fertille de Coutard and Daviana), were analysed by reversed-phase HPLC/DAD for the definition of their phenolic composition. Antioxidant potential was assessed by the reducing power assay, and the scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and b-carotene linoleate model system. Their antimicrobial capacity was also tested against Gram positive (Bacillus cereus, Bacillus subtilis, Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 28 publications
3
63
2
3
Order By: Relevance
“…Daviana cultivar proved to be the most promissory cultivar, presenting the best results, with higher growth inhibition zones and lower MICs. Fruit extracts had a similar antimicrobial activity to hazel leaf extracts for the same cultivars (Oliveira et al, 2007) which were effective at low concentrations (around 0.1 mg/mL); the present extracts are even better than table olive extracts previously studied by us Sousa et al, 2006). The antimicrobial agents added in food generally present problems related to some inherent toxicity (resistance, mutagenesis and carcinogenesis effects, for example) and natural compounds, such polyphenols have gained increasing importance.…”
Section: Antimicrobial Activitymentioning
confidence: 48%
See 2 more Smart Citations
“…Daviana cultivar proved to be the most promissory cultivar, presenting the best results, with higher growth inhibition zones and lower MICs. Fruit extracts had a similar antimicrobial activity to hazel leaf extracts for the same cultivars (Oliveira et al, 2007) which were effective at low concentrations (around 0.1 mg/mL); the present extracts are even better than table olive extracts previously studied by us Sousa et al, 2006). The antimicrobial agents added in food generally present problems related to some inherent toxicity (resistance, mutagenesis and carcinogenesis effects, for example) and natural compounds, such polyphenols have gained increasing importance.…”
Section: Antimicrobial Activitymentioning
confidence: 48%
“…With this regard the antimicrobial capacity of phenolic compounds has also been reported (Rauha et al, 2000;Puupponen-Pimiä et al, 2001;Proestos et al, 2005;Sousa et al, 2006;Pereira et al, 2006Pereira et al, , 2007. In fact, there are recent reports about the antioxidant and antiradical activities in extracts of Turkish hazelnut kernel, hazelnut green leafy cover (Alasalvar et al, 2006b), and other hazelnut byproducts such as hazelnut tree leaf (Oliveira et al, 2007;Shahidi et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalent phenolics accumulates in Corylus avellana kernels and its byproducts are catechin, gallic acid, sinapic acid, caffeic acid, p-coumaric acid, ferulic acid, their esters and flavonoids (Shahidi et al 2007;Del Rio et al 2011). Various other bioactive phenols have also been characterized in hazelnut leaves and foliar buds (Oliveira et al 2007). However, literature survey revealed that jacquemont's hazelnut got very less attention than C. avellana.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing power of the extracts was determined as described by Oliveira et al (2007) with slight modification. Different concentrations (50, 100, 250 and 500 μg/mL) of leaf extracts were mixed with phosphate buffer (2.5 mL, 0.2 M, pH 6.6) and 2.5 mL of 1% potassium ferricyanide.…”
Section: Ferric Ion Reducing Powermentioning
confidence: 99%